Assessment of Genetic Variability, Heritability, Genetic Advance, Correlation and Path Coefficient for Seed Yield and its Component Traits in Indian Mustard [Brassica juncea (L.) Czern and Coss.] - Chauhan, Rahul Singh; Kumar, Mukesh; Tiwari, Mayank; Kumar, Shubham; Chauhan, Vaibhav; Pushpendra, (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during the rabi season (October, 2021–March, 2022) at the crop research centre Sardar Vallabhbhai Patel University of Agriculture and Technology Meerut, Uttar Pradesh, India.The field experiment was conducted with 40 genotypes in randomized complete block design with three replications to assess the genetic variability, heritability, genetic advance, correlation, and path coefficient for seed yield and yield-related traits. The Indian mustard genotypes were evaluated for fourteen quantitative traits. The analysis of variance indicated highly significant variations among the genotypes. The highest estimate of GCV and PCV values were observed for grain yield plant-1. The high level of heritability was recorded for grain yield plant-1, biological yield plant-1, siliquae on main axis, length of main axis, number of secondary branches plant-1, siliqua length, days to 50% flowering, 1000 seed weight and number of seeds siliqua-1. Grain yield plant-1, biological yield plant-1, number of secondary branches plant-1, 1000 seeds weight, length of main axis, siliquae on main axis and siliqua length had the highest genetic advance. The seed yield plant-1 had a highly significant and positive association with biological yield plant-1, number of secondary branches plant-1, siliquae on main axis, number of primary branches plant-1, siliqua length, number of seeds siliqua-1, length of main axis and harvest index. Among fourteen characters studied the biological yield plant-1 recorded the maximum direct effect on seed yield plant-1 (both at genotypic and phenotypic levels).This indicated that yield improvement might be achieved by selection based on these traits.